2013
DOI: 10.1099/ijs.0.048009-0
|View full text |Cite
|
Sign up to set email alerts
|

Amphibacillus iburiensis sp. nov., an alkaliphile that reduces an indigo dye

Abstract: An indigo-reducing alkaliphilic strain, designated strain N314 T , was isolated from a fermented polygonum indigo (Polygonum tinctorium Lour.) liquor sample, aged for 10 months, that was obtained from Date City, Iburi Branch, Hokkaido, Japan. The 16S rRNA gene sequence phylogeny suggested that strain N314 T is a member of the genus Amphibacillus, with the closest relatives being Amphibacillus indicireducens (98.9 % similarity to the type strain) and Amphibacillus xylanus (98.0 % similarity to the type strain),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 37 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the name Amphibacillus iburiensis sp. nov. was proposed for this strain ( Hirota et al, 2013c ; Table 1 ). The species exhibited similar characteristics to Amphi.…”
Section: Indigo-reducing Bacteria Belonging To the Genera Amentioning
confidence: 99%
“…Therefore, the name Amphibacillus iburiensis sp. nov. was proposed for this strain ( Hirota et al, 2013c ; Table 1 ). The species exhibited similar characteristics to Amphi.…”
Section: Indigo-reducing Bacteria Belonging To the Genera Amentioning
confidence: 99%
“…This bacterium showed unique phenotypic and chemotaxonomic characteristics; therefore, it was accepted as a new genus ( Amphibacillus ) and species ( xylanus ) . Presently, nine species belong to this genus . Amphibacillus xylanus grows well under aerobic and anaerobic conditions, exhibiting the same growth rate and cell yields under both conditions, despite its lack of a respiratory chain .…”
mentioning
confidence: 99%
“…Under such extreme conditions, there is a gap between the temperatures suitable for metabolism and those suitable for propagation. For example, it has been reported that Amphibacillus iburiensis can survive at pH values higher than 10.5 and exhibits indigoreducing activity at those pH values (Hirota et al, 2013). However, bacterial propagation is observed at relatively low pH values under laboratory conditions.…”
Section: Geobacillus Thermodenitrificans Dsm 465 T (Z26928)mentioning
confidence: 99%
“…However, bacterial propagation is observed at relatively low pH values under laboratory conditions. Although there was apparent metabolic activity in the form of acid production by the inoculated cells in broth adjusted to a pH value greater than pH 10, actual growth was initiated at pH 8.0-9.1, with optimum growth observed at pH 8.9-9.1 (30°C) (Hirota et al, 2013). Thus, we hypothesize that there are bacterial niches that exhibit temperatures lower than that inside the compost and that the temperature range in which bacteria are able to perform metabolic activity is different from the range in which bacterial propagation can occur.…”
Section: Geobacillus Thermodenitrificans Dsm 465 T (Z26928)mentioning
confidence: 99%